3n+4=-5
do the opposite of adding 4. this means you have to subtract 4 from 4. whatever you do to the problem, you must do to the answer. now subtract 4 from -5.
-5-4=-9
since 4-4=0, we can take 4 out of the equation. now you have:
3n=-9
now divide -9 by 3
-9/3=-3
n=-3
hope this helps :)
I believe it is an exponential function.
Answer:
-13, -12, -11
Step-by-step explanation:
-13 is the lowest, -12 is the middle, -11 is the highest.
-13 + (-12) = -25 + (-11) = -36
Hope this helps! :)
No not always the answer has to be irrational.
<span />
Answer:
11/12
Step-by-step explanation:
2/3+1/4
8/12+3/12= 11/12